Mechanochemical synthesis of sodium doped hydroxyapatite powder - Syed Abu Bakar, Sharifah Adzila; Sopyan, Iis; Singh, Ramesh; Pusparini, Erlani (Scientific Publishers of India, 2013)
Bioactive hydroxyapatite (HA) with nanosized spherical shape has been synthesized through mechanochemical synthesis of calcium hydroxide and diammonium hydrogen phosphate. Sodium ion has been doped into HA by using sodium hydroxide precursor in a dry mixture of Ca(OH)2 and (NH3)2HPO4. Both Na-free HA and Na-doped HA (1% - 9%) are characterized by X-ray diffraction and Fourier transform infrared analyses. Reduction of the peak intensity and adsorption bands is observed with increasing Na+ concentration in the Na-doped HA structure. Increasing Na+ content expands the lattice parameters and unit cell volume of HA, while the crystallite size and degree of crystallinity decrease with increasing Na+ level. A mixture of rods and spheres are found in the Na+ doped HA. Characterization of the obtained powder suggests that Na doped HA has a potential to be used in clinical applications.